1977
DOI: 10.1084/jem.145.1.76
|View full text |Cite
|
Sign up to set email alerts
|

Specific binding of soluble fibrin to macrophages.

Abstract: Clearance of microparticulate fibrin by the reticuloendothelial system has been long recognized as a defense mechanism against intravascular fibrin deposition (1, 2). In general this has been assumed to be part of the relatively nonspecific phagocytic process whereby the reticuloendothelial system removes other microparticulate material such as bacteria, from the circulation. Numerous in vitro studies (3-7) have documented the fact that before formation of particulate fibrin, fibrin may exist in a soluble form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

1979
1979
2001
2001

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…Many studies have shown that fibrinogen can bind to and induce migration of a large range of cell types to penetrate the wound and repair the site (Altieri et al, 1986(Altieri et al, , 1993Dejana et al, 1985;Plow & Edgington, 1986;Sherman & Lee, 1977;Skogan et al, 1988). Biopsies of tissues from the afibrinogenaemic mice showed fibriotic capsules around, but not penetrating, hepatic and renal haematomas.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that fibrinogen can bind to and induce migration of a large range of cell types to penetrate the wound and repair the site (Altieri et al, 1986(Altieri et al, , 1993Dejana et al, 1985;Plow & Edgington, 1986;Sherman & Lee, 1977;Skogan et al, 1988). Biopsies of tissues from the afibrinogenaemic mice showed fibriotic capsules around, but not penetrating, hepatic and renal haematomas.…”
Section: Discussionmentioning
confidence: 99%
“…If correct, then fibrin(ogen) is likely to play a key role in the pathobiology of common diseases that promote or result from chronic tissue injury, including cancer, atherosclerosis, and sickle cell disease. Notably, fibrin(ogen) is a significant component of atherosclerotic lesions (Bini and Kudryk 1992) and interacts with many of the cells that appear to contribute to plaque development, including platelets, endothelial cells, macrophages, leukocytes, and smooth muscle cells (Sherman and Lee 1977;Wright et al 1983;Dejana et al 1985;Altieri et al 1986;Bennett 1991;Naito et al 1992;Majerus 1994). Nevertheless, the lack of a suitable in vivo system for manipulating fibrinogen levels and/or its functional properties has precluded definitive studies regarding a role of fibrin(ogen} in atherogenesis.…”
mentioning
confidence: 99%
“…First, a variety of cell types specifically bind to and migrate on fibrin(ogen) matrices, including endothelial cells (Dejana et al 1985), macrophages (Sherman and Lee 1977;Altieri et al 1986), leukocytes (Wright et al 1983;Altieri et al 1993), smooth muscle cells (Naito et al 1992), fibroblasts (Brown et al 1993), keratinocytes (Donaldson et al 1994}, and tumor cells (Dvorak 1986;Dvorak et al 1992). Direct binding to fibrin(ogen) through both integrin [e.g., ~v~3, aM~2 (Mac-l); Altieri et al 1993, Simon et al 1993Katagiri et al 1995] and non-integrin receptors (e.g., I-CAM-l; Languino et al 1995) appears to contribute to these cell-fibrin interactions.…”
mentioning
confidence: 99%
“…These include emigration of lymphocytes, local lymphoblast transformation, and the profound endothelial activation/ necrosis and basement membrane thickening of the small dermal vessels cuffed by these cells. Fibrin deposits might be expected to exert some influence on the cellular infiltrate because macrophages have surface receptors for fibrin/fibrinogen (19,20), but recognizable macrophages are uncommon in delayed reactions in man (9) and alterations in these cells would be difficult to evaluate.…”
Section: Discussionmentioning
confidence: 99%
“…is a 32-yr-old Caucasian male with afibrinogenemia who has been reported (6,7). His plasma does not form a visible clot, although the presence of fibrinogen has been detected at minimal levels by hemagglutination (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) ,ug/ml, <1% normal). He has had occasional traumatic intramuscular hemorrhages, which usually do not require fibrinogen therapy.…”
Section: Methodsmentioning
confidence: 99%